Bullying-Related Social Skills Instrument: within the Extracurricular Activities in Educational Context - Arini, Fitri Dwi (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2021)
The purpose of this study is to develop an instrument to measure the level of social skills of children with disabilites related to bullying behavior. This is a developmental research, where the instruments that was developed is in the form of self-assessed questionnaire. The social skills instrument developed was using four dimensions that strongly related to bullying behavior, namely, emphaty, self-control, assertiveness, and cooperation. The development process were following four stages. First, a literature review was conducted for constructing the operational definition. Items for the instrument were 3 point Likert-type. The instruments then validated by peer evaluation and its reliability measured using internal consistency method. The result of the study is an instrument measuring the bullying-related social skills which ideally used within the extracurricular activities context where all children gather to socialized in a controlled environment.